Twenty new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental Region - Jendek, Eduard; Grebennikov, Vasily V. (Zootaxa, 2018)
Twenty new Agrilus species from the Oriental Region are described and illustrated: A. aramis sp. nov. (Laos), A. aries sp. nov. (Laos), A. armipes sp. nov. (Laos, India), A. athos sp. nov. (Laos, Thailand), A. bacan sp. nov. (Indonesia), A. bicolorifrons sp. nov. (Laos), A. cuprocunctus sp. nov. (Laos), A. ebenus sp. nov. (Laos, Thailand, Vietnam), A. frontis sp. nov. (Laos), A. gemellus sp. nov. (Nepal), A. khunborom sp. nov. (Laos), A. kyklos sp. nov. (Laos), A. loongfahi sp. nov. (Malaysia), A. metallinus sp. nov. (Laos), A. nemoralis sp. nov. (Laos), A. porthos sp. nov. (Laos), A. princeps sp. nov. (Laos), A. rex sp. nov. (Malaysia), A. sikhiav sp. nov. (Laos) and A. sinuosus sp. nov (Laos, Vietnam).